Implementasi Model Problem Based Learning untuk Meningkatkan Hasil Belajar pada Kompetensi Tata Rias Wajah Geriatri di SMK Negeri 1 Pogalan - Dhea Noor Yucha Ana Dhea; Dindy Sinta Megasari; Nia Kusstianti; Nieke Andina Wijaya (Jurnal Tata Rias, 2026)
Learning geriatric facial makeup in vocational high schools requires mastery of concepts, analysis of elderly skin characteristics, and accurate technical skills. However, conventional learning methods have not fully optimized students’ learning outcomes. This study aimed to implement the Problem Based Learning (PBL) model to improve learning outcomes in geriatric facial makeup competency at SMK Negeri 1 Pogalan. The research employed a Classroom Action Research design conducted in two cycles. The research subjects consisted of 34 eleventh-grade students of the Skin and Hair Beauty program. Data were collected through cognitive tests (pretest and posttest), performance tests, and observation sheets on the implementation of PBL syntax. Data analysis was conducted using descriptive quantitative methods. The results indicated an improvement in the implementation of PBL syntax, with the average score increasing from 3.86 in Cycle I to 3.93 in Cycle II, categorized as very good. Cognitive learning outcomes also improved, as shown by the increase in the average pretest score from 65.88 to 71.47 and the average posttest score from 85.44 to 89.11, with classical learning mastery achieved in Cycle II. In addition, students’ performance skills showed improvement, with the performance test score increasing from 34.61 to 34.79 and the average score remaining in the very good category.It can be concluded that the implementation of the Problem Based Learning model is effective in improving both cognitive learning outcomes and performance skills in geriatric facial makeup competency. This model is relevant for vocational education as it emphasizes real-world problem solving and the strengthening of practical skills. Keywords: Problem Based Learning, learning outcomes, geriatric facial makeup, vocational high school